PELATIHAN PENELITIAN TINDAKAN KELAS DALAM UPAYA PENINGKATAN PROFESSIONALITAS GURU SEKOLAH DASAR PPG DALJAB KATEGORI 1 TAHUN 2022, LPTK UNIV JEMBER - Sri Kantun; Retna Ngesti Sedyati; Jefri Rieski Triyanto; Irmadatus Sholekhah (P3M Politeknik Negeri Malang, 2022)
This service aims to provide knowledge and skills to elementary school teachers about efforts to improve the professionalism of elementary school teachers through classroom action research. Classroom action research was chosen because the research is considered simple and very easy to implement for elementary school teachers. This service provides knowledge to participants about the basic concepts of classroom action research and research methods, as well as preparing CAR reports. The methods used in this service are lectures and demonstrations. Based on the results of this service, it was concluded that elementary school teachers were very enthusiastic and interested in classroom action research. This is evidenced by the many questions to the informants. In addition, the number of participants who attended was 35 people, indicating that elementary school teachers were very interested in this training. Participants become more aware of the basic concepts of classroom action research and the systematics of preparing reports, because so far elementary school teachers consider CAR as a difficult research.